Pengembangan Media Pembelajaran Booklet Pada Materi Sistem Pencernaan Pada Manusia Kelas VIII SMP Negeri Neonbat - fransiska ermalinda elu (JBIOEDRA: Jurnal Pendidikan Biologi, 2024)
The aim of this research is to 1) Find out the development of booklet learning media on digestive system material for class VIII humans of SMP Negeri Neonbat Junior High School. 2) Find out the feasibility of booklet learning media for class VIII human digestive system material at SMP Negeri Neonbat Junior High School. This research uses a type of research and development (R&D). Research and development is a process or steps to develop a new product or improve an existing product, which can be accounted for. The steps in this research include 2 stages, namely stage I, the preliminary study stage and stage II, the model development stage. The instrument used in the research was a questionnaire. The purpose of using a questionnaire is to determine the feasibility of the product being developed. The trial subjects in this research were 1 media expert validator and 1 material expert validator, tested on 3 science teachers and individual trials consisting of 5 students and small group trials consisting of 24 class VIII students at SMP Negeri Neonbat State Middle School. The booklet learning media that was developed was very suitable for use with a percentage from media experts of 79.68% in the (feasible) category, validation results by material experts obtained a percentage of 98.52% in the (very good) category, trial results for science teachers were 72,72% by category (eligible). Individual trial results obtained a percentage of 89.33% in the (very good) category. The results of the trial on the small group obtained a percentage of 91,04% in the (very good) category. Based on the results of the data obtained, it can be concluded that the resulting booklet learning media product meets the valid qualifications and is suitable for use as teaching material in supporting the teaching and learning process on the Digestive System in Humans class VIII SMP Negeri Neonbat.